Perancangan Sistem Informasi Pendaftaran Ekstrakurikuler Berbasis Web Pada SMK Malaka Jakarta - Ade Suryanto; Ramadon Ramadon (Paradigma, 2018)
The development of technology and information is very helpful in an organization. Extracurricular organizations in Malaka Vocational High School Jakarta in the registration information system still use manual system or not yet computerized, it caused the lack of effective and efficient registration information. So the need for information system registration extracurricular effective and efficient with computerized a system using a website-based, to help facilitate the management of registration information and extracurricular data member. To develop an extracurricular registration information system using waterfall method. The test results show that the information system capable of conducting online extracurricular registration process can be effective and efficient.